Development Of A Model Of Utilizing Cash Wakaf To Realize A Legal Tourism Area In Medan City - Faisal Faisal; Zainuddin Zainuddin; Nursariani Simatupang; I. Koto; Ismail Sitorus (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Today's cash waqf has become one of the financing alternatives for fiscal instruments in the economy. The understanding of the benefits of waqf, which so far has only been used for direct worship facilities such as mosques and cemeteries, has shifted in a broader direction, especially to improve welfare and the economy. Cash waqf has two functions: as a means of worship and as a means of improving social welfare. Returns from the management of cash waqf can be used as instruments in poverty alleviation programs through the development of MSMEs and the establishment of tourist areas. The impact of developing tourist areas will be felt directly by the community if, in these tourist areas, MSMEs grow and develop. The utilization of productive waqf with the management of Hajj funds is in accordance with the intent of Law Number 34 of 2014 concerning Hajj Financial Management and Law Number 41 of 2004 concerning Waqf, both of which aim to provide benefit to Muslims. In its implementation, the utilization of waqf funds can be made into a hotel project or infrastructure supporting halal tourism, such as airports, MSME kiosks, and so on. Then the profits obtained will be channeled for the benefit of the people. On the other hand, the development of halal tourism facilities and infrastructure also creates jobs. In addition, Indonesia is already known as a Muslim-friendly tourist destination. This development of halal tourism can optimize Indonesian tourist destinations as Muslim-friendly tourist destinations. Cash waqf as a means of financing can be used for more than one particular sector and only certain models. Cash waqf can be used as an alternative solution for financing all sectors that support the economy, both for consumptive and productive purposes. The benefits of cash waqf for the productive sector can be realized by increasing community capital in developing their businesses, both for basic business capital and for supporting capital for their businesses. What about the attractive design and appearance of the area surrounding where they are attempting to become a community destination for visiting?